Comparison Method Between the Finite Element Method and the Henssge Model Method in Estimating the Time of Death - Yahya, Mazaya Wani; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2025)
Estimating the time since death (TSD) is a fundamental aspect of forensic investigations, as it provides crucial information for reconstructing events leading to a person’s death. Traditional methods, such as the Henssge model, estimate TSD based on postmortem body cooling but often struggle with complex environmental conditions. This study compares the Henssge model with the Finite Element Method (FEM), a numerical approach that simulates heat transfer mechanisms like conduction, convection and radiation. Using MATLAB, the accuracy of both methods was evaluated based on five forensic cases analysed by Mall and Eisenmenger (2005). Results indicate that FEM consistently provides more precise estimates, particularly in scenarios involving sudden temperature changes, clothing insulation and body repositioning. Statistical error analysis further supports FEM’s advantages, with significantly lower mean absolute error (MAE) and root mean square error (RMSE) compared to the Henssge model. These findings confirm that FEM is a more reliable alternative for forensic time since death estimation and offers improved accuracy in real-world forensic applications.